Emory's gift - Cameron, W. Bruce (New York, NY : Forge, 2011)
In 1974, when thirteen-year-old Charlie Hall's mother dies and his father retreats into silent grief, Charlie finds himself drifting, nearly friendless, through a northern Idaho junior high school but when a grizzly bear saves his life, Charlie forms an unusual friendship that changes his life.
"A Tom Doherty Associates Book."
Keywords: Human-animal relationships -- Fiction; Grief -- Fiction; Grizzly bear -- Fiction; Bears -- Fiction; Junior high schools -- Fiction; Schools -- Fiction; Family life -- Idaho -- Fiction; Idaho -- History -- 20th century -- Fiction